Single and interactive effects of variables associated with climate change on wheat metabolome - Večeřová, Kristýna; Oravec, Michal; Puranik, Swati; Findurová, Hana; Veselá, Barbora; Opoku, Emmanuel; Ofori-Amanfo, Kojo Kwakye; Klem, Karel; Urban, Otmar; Sahu, Pranav Pankaj (Frontiers in Plant Science, 2022)
One of the key challenges linked with future food and nutritional security is to evaluate the interactive effect of climate variables on plants’ growth, fitness, and yield parameters. These interactions may lead to unique shifts in the morphological, physiological, gene expression, or metabolite accumulation patterns, leading to an adaptation response that is specific to future climate scenarios. To understand such changes, we exposed spring wheat to 7 regimes (3 single and 4 combined climate treatments) composed of elevated temperature, the enhanced concentration of CO2, and progressive drought stress corresponding to the predicted climate of the year 2100. The physiological and metabolic responses were then compared with the current climate represented by the year 2020. We found that the elevated CO2 (eC) mitigated some of the effects of elevated temperature (eT) on physiological performance and metabolism. The metabolite profiling of leaves revealed 44 key metabolites, including saccharides, amino acids, and phenolics, accumulating contrastingly under individual regimes. These metabolites belong to the central metabolic pathways that are essential for cellular energy, production of biosynthetic pathways precursors, and oxidative balance. The interaction of eC alleviated the negative effect of eT possibly by maintaining the rate of carbon fixation and accumulation of key metabolites and intermediates linked with the Krebs cycle and synthesis of phenolics. Our study for the first time revealed the influence of a specific climate factor on the accumulation of metabolic compounds in wheat. The current work could assist in the understanding and development of climate resilient wheat by utilizing the identified metabolites as breeding targets for food and nutritional security.